TMJ replacement utilizing patient-fitted TMJ TJR devices in a re-ankylosis child. Issue 4 (April 2016) - ,; Giancotti, A.; Castori, M.; Lenzi, J.; Manganaro, L.; Papoff, P.; Pizzuti, P.; Polimeni, A.; Roggini, M.; Tarani, L.; Silvestri, A.; Cascone, Piero; et al.
Abstract: Temporomandibular joint (TMJ) ankylosis is a pathological condition characterized by articular bony or fibrous tissue fusion. TMJ ankylosis developing during childhood can lead to growth complications because of the loss of mandibular function. Hard and soft autogenous tissue grafting has been used for TMJ reconstruction in the growing patient. However, in cases where autogenous tissue grafts fail either due to unpredictable growth or ankylosis, total alloplastic temporomandibular joint replacement (TMJ TJR) can provide a viable option. The case of a 7-year old female suffering from recurrent bilateral TMJ ankylosis resulting from birth trauma, and with concomitant obstructive sleep apnea syndrome (OSAS) is presented. Due to prior surgical and autogenous graft failures, the decision was made to complete her joint reconstructions utilizing patient-fitted TMJ prostheses. Questions have been raised about the longevity of TMJ TJR devices as well as their lack of growth potential, but children with TMJ ankylosis do not have condyle-related growth potential and that replacing failed autogenous tissue graft material with more autogenous tissue will result in the same adverse outcomes. Therefore, in growing patients with recurrent TMJ ankylosis and/or failed autogenous tissue grafts, there may be a role for TMJ TJR.